Forecasting Human Development Index With Double Exponential Smoothing Method And Acorrect Determination - Agum Surya Ramadhan; Agung Prabowo; Rabiu Hamisu Kankarofi; Ibrahim Mohammed Sulaiman (International Journal of Business, Economics, and Social Development, 2023)
Human development is now seen as a measure of the success of the development of a nation which is closely related to the economic, social, cultural, political and environmental fields. The success of human development is measured based on the Human Development Index (IPM). Boyolali Regency is one of the regencies in Central Java Province which has diverse and abundant natural resources. The large potential of natural resources owned should be in line with the quality of human development. However, it turns out that this is not in line with the HDI value of Boyolali Regency which is still below the average HDI value of Central Java. So that the Boyolali government continues to strive to maximize the potential and increase the HDI value. Based on this, it is necessary to do forecasting as a reference to maximize the level of human development in Boyolali Regency in the next few years. In this study, HDI forecasting in Boyolali Regency was carried out using the Double Exponential Smoothing method from Brown with the data used is HDI data in Boyolali Regency from 2011 to 2021. The data used was obtained from the Central Bureau of Statistics (BPS) Boyolali Regency. HDI forecasting was also carried out using the arithmetical method, and the best forecasting results were compared between the two methods based on the mean absolute percentage error (MAPE). Forecasting results using the Double Exponential Smoothing method produce the best alpha smoothing parameter values of 0.91 and MAPE values of 0.4061%. Meanwhile, using the arithmetic series method, the MAPE is 0.4704%. Both methods produce MAPE values with very good criteria, so that both methods can be used for forecasting. However, based on the criteria for the smallest MAPE value, the Double Exponential Smoothing method is used. The results of the HDI forecasting using the Double Exponential Smoothing method for 2022, 2023 and 2024 are 74.61, 74.81 and 75.02 respectively. While the results of forecasting with arithmetical method for the same years are 74.93, 75.45, and 75.98.